Leadership Style and Organizational Culture on Employee Productivity Mediated by Work Motivation - Chandra Budiman Zain; Ferikawita M. Sembiring (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2025)
PT TRFood, despite its strong product capacity and market recognition, faces significant challenges in employee management, particularly within the production and distribution divisions. Accordingly, this study aims to analyze the influence of leadership style and organizational culture on employee productivity, with work motivation as a mediating variable. The research employed descriptive and verification approaches. The population consisted of all 338 employees, and the sample of 184 employees was selected through purposive sampling. Data were collected using observation, questionnaires, documentation, and literature review, with the questionnaire serving as the main instrument. Path analysis was applied to examine the relationships among variables. The findings indicate that while leadership practices, organizational culture, and employee motivation have been implemented adequately, they have not yet reached an optimal level in enhancing productivity. First, leadership style has a positive influence on employee productivity. Second, organizational culture positively affects employee productivity. Third, leadership style positively influences work motivation. Fourth, organizational culture positively affects work motivation. Fifth, work motivation positively influences employee productivity. Overall, the study concludes that leadership style, organizational culture, and work motivation simultaneously exert a positive effect on employee productivity.